Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae) - Carrillo-Lara, Diana E.; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2018)
The last larval stadium of Orthemis ferruginea (Fabricius, 1775) is described and illustrated in detail based on reared material collected in the municipality of Paso de Ovejas, Veracruz, Mexico. It is compared with larvae of other species of the genus previously described. The main structural features are the number of setae on palp, prementum and palp crenations, the size proportion of cerci respect to epi- and paraprocts, and the number of sclerites on abdominal sternum 5.